Archetypes in Architecture - Thomas Thiis-Evensen (Scandinavian University Press (Universitetsforlaget), 1987)
This book develops a grammar for the basic elements in the art of building: the floor, the wall and the roof. Drawing on examples from the history of architecture, a range of archetypes connected to these basic elements are discussed. The book explores how these architectural archetypes affect us psychologically, with a particular emphasis on the relationship between archetypes and the dynamic interactions between inside and outside space. The book shows how our experiences of architecture are tied in with our bodily experiences of archetypes as carriers of specific meanings, which in turn influences our experiences of the relationship between inside and outside. The aim of the book is design-oriented. With more accurate knowledge of the archetypes and their variations, schematic post-war architecture can be replaced without necessarily resorting to copying motifs from the past.